WHAT DOES 'CONSISTENT' MEAN IN THE SHORT FORM REPORT? - Borth, Daniel (The Accounting Review, 1948)
Abstract The lack of exceptions, qualifications, or explanations concerning consistency is somewhat disturbing to the critical reader in a period of rapidly changing economic conditions from phase of the business cycle to another. From one tax law to another with changes in products, distribution methods, and administrative organization, with changes from a controlled economy to one of relative freedom, with labor unrest, inflation, and unsettled international economic conditions, it would seem that an audit would quite often result in some material differences of opinion on accounting principles which failed of reconciliation. The principles of accounting so consistently applied by corporate management that the residual unresolved differences of opinion are almost invariably minor in character and not deserving of mention in the accountant's opinion report of the public accountant which can almost invariably declare that generally accepted accounting principles are applied on a basis consistent with that of the preceding year.